Dynamics of Tax Avoidance in ASEAN: Thin Capitalization, Inventory Intensity, And Ownership of Intangible Assets Moderate by Profit Management - Saputra, Winnendra Dwi; Izati, Elis Nur; Reskino, Reskino (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the influence of thin capitalization, inventory intensity, and ownership of intangible assets on tax avoidance. This research uses secondary data from manufacturing companies listed on the stock exchanges of ASEAN countries in the 2017-2021 period, with a sample of 723 companies. The sample selection technique uses a purposive sampling method and data is analyzed using a Structural Equation Modeling (SEM) approach with the Partial Least Squares (PLS) application. The results of this study show that thin capitalization has no significant effect on tax avoidance, while inventory intensity and ownership of intangible assets have a significant positive effect on tax avoidance, and earnings management is proven to be able to weaken the effect of thin capitalization, inventory intensity and ownership of intangible assets on tax avoidance.